Transient behavior of two-stage load rejection for multiple units system in pumped storage plants. (November 2020) - Chen, Sheng; Wang, Jing; Zhang, Jian; Yu, Xiaodong; He, Wei
Abstract: Pumped storage plants (PSPs) are being rapidly deployed and developed since they are cost-effective and mature energy storage solutions to the penetration of renewable energy sources (RES). Hydraulic transient analysis on PSPs, especially under extreme operating conditions such as two-stage load rejection (LR), is the key to safe hydraulic system design. Two-stage LR, involving a step-wise reduction in load, may induce extremely low draft tube pressure (DTP), directly threatening the safety of a multiple units PSP. Using numerical simulation, this study systematically investigates the behavior of the hydraulic parameters, and reveals the mechanism leading to the extremely low DTP during a two-stage LR process. The results indicate that the asynchronously varying discharge, coming from the inconsistent instants of time rejecting load and subsequent pressure difference, is the origin of severe reverse water hammer. Furthermore, the rate of discharge change of the subsequent load rejection turbine (SLRT) is confirmed to be the critical factor. The unexpected low DTP occurs exactly when its rate of discharge change reaches its minimum value. Additionally, the deeper the moving trajectory of the SLRT enters the reverse pump zone, the more severe the low DTP will be. Finally, two engineering measures that can economically and effectively improve the minimum DTP are proposed based on the hydraulic behavior of two-stage LR. Highlights: Unexpected fact that extremely low DTP of SLRT can be induced under two-stage LR is presented. Whole fluid transients during two-stage LR is presented, and the corresponding hydraulic behavior is detailed analyzed. Mechanism and critical factor leading to tremendous pressure fluctuation during two-stage LR is presented. Characteristics of worst instant is analyzed from the viewpoint of the moving trajectory on characteristic curves. Two engineering measures that can effectively mitigate pressure fluctuations are proposed.